2014
DOI: 10.1111/jpn.12266
|View full text |Cite
|
Sign up to set email alerts
|

Feeding practice and influence on selected blood parameters in show jumping horses competing inSwitzerland

Abstract: The aim of this study was to compare the nutritional management of show jumping horses in practice with recommendations from the literature. Additionally, the effects of these feeding practices on several blood metabolic parameters before and after exercise were studied. Blood samples were collected in the field from 27 different horses at 71 trials on the level M1 to S2 show jumping competitions in Switzerland and questionnaires on feeding practice of the studied horses were evaluated. The questionnaires reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 34 publications
1
15
0
1
Order By: Relevance
“…It is possible that the hay offered does not adequately represent the hay consumed and is overestimated; however, no representatives reported significant wastage. The findings of a mix of commercial feeds and "raw" ingredients such as cereal grains and by-products appear to be consistent with previous research [3,4].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…It is possible that the hay offered does not adequately represent the hay consumed and is overestimated; however, no representatives reported significant wastage. The findings of a mix of commercial feeds and "raw" ingredients such as cereal grains and by-products appear to be consistent with previous research [3,4].…”
Section: Discussionsupporting
confidence: 93%
“…This study certainly does not include all the world-class horses of this discipline nor does this study includes horses that were competing at lower levels. Despite this, the present study included data from more elite horses than previously reported studies [3,4].…”
Section: Discussionmentioning
confidence: 47%
See 2 more Smart Citations
“…() reported sampling frequency as a consideration for further research measuring glucose and insulin levels when studying performance horse diets. Brunner, Liesegang, Weiss, and Wichert () documented that even the timing of feeding forages significantly influenced blood glucose concentrations and free fatty acids, and thus, that will need to be considered when determining the timing and frequency of blood sampling.…”
Section: Discussionmentioning
confidence: 99%